2007
DOI: 10.5194/hess-11-108-2007
|View full text |Cite
|
Sign up to set email alerts
|

Characterising groundwater-dominated lowland catchments: the UK Lowland Catchment Research Programme (LOCAR)

Abstract: This paper reports on a major UK initiative to address deficiencies in understanding the hydro-ecological response of groundwater-dominated lowland catchments. The scope and objectives of this national programme are introduced and focus on one of three sets of research basins the Pang/Lambourn Chalk catchments, tributaries of the river Thames in southern England. The motivation for the research is the need to support integrated management of river systems that have high ecological value and are subject to pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 8 publications
(11 reference statements)
0
35
0
Order By: Relevance
“…There was a clear difference between the variograms in the horizontal and vertical planes. Therefore the estimated model was isotropic in the horizontal plane with geometric anisotropy in the vertical plane (Webster and Oliver, 2007). The estimated spherical variograms are shown in Figure 2b …”
Section: D Peat Temperature Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…There was a clear difference between the variograms in the horizontal and vertical planes. Therefore the estimated model was isotropic in the horizontal plane with geometric anisotropy in the vertical plane (Webster and Oliver, 2007). The estimated spherical variograms are shown in Figure 2b …”
Section: D Peat Temperature Modelmentioning
confidence: 99%
“…Studies at a nearby site 100 m upstream of the Observatory, part of the Lowland Catchment Research (LOCAR) programme (Wheater, et al, 2007), have indicated variable hydraulic connection between the Chalk, gravels and surface water (Abesser, et al, 2008;Allen, et al, 2010;Lapworth, et al, 2009). The extent of the interaction remains unclear.…”
Section: Initial Conceptual Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this behaviour might be due to the modelling assumption of a constant vertical porosity, despite the knowledge that there can be a strongly non-linear relation between chalk transmissivity and depth. Several studies acknowledge that hydraulic conductivity in the Chalk follows a non-linear decreasing trend with depth (Allen et al, 1997;Wheater et al, 2007;Butler et al, 2009). This is mainly attributed to the decrease in fractures because of the increasing overburden and absence of water level fluctuations Butler et al, 2012).…”
Section: Performance Of the Percentile Approachmentioning
confidence: 99%
“…As a consequence of their stable flow regimes, intensive abstraction for public and agricultural water supply and extensive growth of aquatic vegetation, chalk rivers are fluvial environments that are particularly vulnerable to problems associated with the storage of fine sediment (Wheater et al, 2007). These rivers support valuable aquatic and riparian ecosystems, so are recognized as a priority habitat for protection under the UK Biodiversity Action Plan (Mainstone and Parr, 2002;Wright et al, 2002).…”
Section: M Heppell Et Almentioning
confidence: 99%